Debate over the importance and meaning of native range in invasion biology: reply to Courchamp et al. - Pereyra, Patricio Javier (2020)
CommentDebate over the importance and meaning of nativerange in invasion biology: reply to Courchamp et al.Patricio Javier Pereyra1,2,3∗and Radu Cornel Guia¸su41Centro de Investigación Aplicada y Transferencia Tecnológica en Recursos Marinos Almirante Storni (CIMAS), San Antonio Oeste,RioNegro,Argentina2Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Ciudad Autónoma de Buenos Aires, Argentina3Escuela Superior de Ciencias Marinas, Universidad Nacional del Comahue, San Antonio Oeste, Rio Negro, Argentina4Biology Program, Glendon College, York University, 2275 Bayview Avenue, Toronto, Ontario, M4N 3M6, CanadaIn their response to Pereyra (2020), Courchamp et al.(2020) considered problems with the concept of nativerange in invasion biology. They start by agreeing withPereyra that the concept of native range has limitations,but then proceed to criticize the work for what theyperceive as “flawed logical reasoning,” “a misleading se-lection of examples,” “cherry picking,” and a failure toappreciate the usefulness of this admittedly poorly de-fined concept. Here, we respond to the criticisms ofCourchamp et al., while addressing the important prob-lems that remain with the application of the native rangeconcept.